The new baby at your house - Cole, Joanna; Miller, Margaret, 1945- (New York : Mulberry Books, 1999)
Describes the activities and changes involved in having a new baby in the house and the feelings experienced by the older brothers and sisters.
"A Mulberry paperback book."
Keywords: Infants -- Juvenile literature; Brothers and sisters -- Juvenile literature; Babies; Brothers and sisters; Infants; Brothers and sisters